Comparative Assessment of Biomass and Power-to-Gas Processes Integrated with Different Electricity-Driven Gasification Technologies - Guohui Song; Xiaobo Cui; Liang Wang; Zheng Wei (Clean Technologies)
To develop a biomass and power-to-gas (BPtG) process for renewable electricity storage and sustainable synthetic natural gas (SNG) production, this work investigated five BPtG processes integrated with different electricity-driven gasification technologies based on simulation data. These processes were evaluated for SNG composition and yield, life-cycle energy and exergy efficiencies, life-cycle carbon emissions, and the equivalent unit production cost. The results show that the energy and exergy efficiencies of SNG from those processes range between 53.1 and 58.6% and 36.4 and 41.1%, respectively. Based on the energy allocation method, the carbon emissions without and with CO2 capture ranges from 22.0 to 34.8 and from −43.4 to −17.6, respectively, in gCO2e/MJSNG. These BPtG processes can produce low-carbon SNG and even achieve negative carbon emissions with CO2 capture. Both feedstock and electricity costs have significant influences on the profitability of the processes. The BPtG process integrated with resistance heating gasification, plasma-assisted gasification, and moderate water electrolysis are recommended for their compromise of multi-perspective performances. This paper provided the orders of the five processes based on these indicators and recommendations for different applicable scenarios.